Comparison of Swedish nurses' attitudes toward involving families in care over a decade - Hanne Konradsen; Zarina Nahar Kabir; Anne-Marie Boström; Kristofer Årestedt (BMC, 2022)
Abstract Background Involving families in care benefits both patients and their families. Sweden was one of the first countries to introduce family nursing, but its effect on nurses' attitudes toward involving families in care was unknown. First, this study aimed to investigate registered nurses' attitudes about the importance of involving families in nursing care. Second, it aimed to compare these attitudes over a decade. Methods This comparative study was based on data from two separate studies. Data were collected using the Families Importance in Care - Nurses' Attitudes questionnaire. The first phase of data collection took place in 2009, and the second phase was conducted in 2019. Results Overall, the nurses were positive towards involving families in care, both in 2009 and 2019. Overall, no significant difference was found between the two studies from 2009 and 2019. On a subscale level, nurses reported significantly higher levels on family as a resource in the study from 2009 compared to the study from 2019. The opposite was shown for the subscales family as a burden and family as an own resource. According to the R 2 values (0.002 - 0.04), the effect sizes were small. Conclusion In Sweden, nurses' attitudes toward involving families in care did not change over the studied decade, despite changes in nursing, healthcare-system, and society.